“Vojvodina nation”. Ideological motive and anti-historical narrative - Marković, Saša (Sociološki pregled, 2022)
The paper represents the historiographic facing with the narrative about the need to construct the “Vojvodina nation”. This narrative, aware of the need for validity and historical persistence, searches for a foundation in its specific interpretation of historiography. The starting point can be found in the acceptance of the historical context of the emancipation of the Serbian national idea in the Habsburg Monarchy. Such discourse is also applied to the Yugoslav state organization, regardless of its divergent character in relation to the Austro-Hungarian Monarchy and the circumstances of the liberation and defence war, in which quite a harmonized national interest of Serbs was realized about unity in the joint state. The ideological prejudice about the meta-ethnic character of Yugoslav unity prevailing after the victory of the socialist revolution, led to the federalist concept of the state organization created on the ruins of the alleged “Great Serbian” national idea. Despite intentions, the circumstance of the socialist building of the Yugoslav society did not prevent the development of nationalist ideas of party bureaucrats. It was a prerequisite for the development of Vojvodina statism and national-building.
Keywords: Serbs; Vojvodina; nation; development